USE OF ANTIOXIDANTS IN PHYSICAL TRAINING. (Fiep Bulletin - online, 2011)
This study aimed to characterize foods with antioxidant potential, using available material on the Scielo's database from 1990 to the present time and to assess the antioxidant actions of the cellular catalyses enzyme in foods. The activity evaluation of the catalyses enzyme was carried out from the degradation of the hydrogen peroxide. The data obtained in the bibliographic research demonstrates a direct relationship between physical activity, especially the exhaustive exercise, and the production of free radicals. The tests for the presence of catalyses were positive in all foods analyzed. The thermal test for catalyses demonstrated the inactivity of the enzyme in the three foods tested, due to high temperature. The results of this research show a direct relationship between physical activity, especially the exhaustive exercise, and the production of free radicals. Also underscore the importance of using antioxidants to neutralize free radicals. But there is a need for more studies on the subject.
Keywords: nutrition; training; and antioxidants